Current status of robotic surgery for pancreatic tumors - Sung Ryol Lee; Jaewoo Kwon; Jun Ho Shin (Society of Gastrointestinal Intervention, 2022)
Robotic pancreatectomy, which has received attention in recent years, is subdivided into robotic distal pancreatectomy and robotic pancreatoduodenectomy. Benign and borderline malignant pancreatic tumors can be treated with robotic pancreatectomy, which has several advantages inherent to robotic surgery. The indications for robotic pancreatectomy are similar to those of laparoscopic pancreatectomy, and there are no absolute contraindications. The perioperative outcomes of robotic pancreatectomy are comparable to those of open or laparoscopic pancreatectomy. A high spleen preservation rate, low intraoperative blood loss, and a low open conversion rate are advantages of robotic pancreatectomy. Although robotic pancreatectomy is possible for the treatment of pancreatic cancer, appropriate case selection is required, and more research is needed.